Continuous flow synthesis and cleaning of nano layered double hydroxides and the potential of the route to adjust round or platelet nanoparticle morphology - Flegler, Andreas; Schneider, Michael; Prieschl, Johannes; Stevens, Ralph; Vinnayd, Thomas; Mandel, Karl (RSC Advances, 2016)
Here, we report a continuous flow synthesis of nano LDH, comprising a continuous precipitation process using static mixers and followed by an immediate cleaning process via a semi-continuous centrifuge to obtain the final product in one-go. Via this synthesis setup, it is possible to independently vary the concentrations of the reactants during precipitation and at the same time ensure constant reaction conditions and an immediate "quenching" of the precipitate due to "on the flow"-washing. We found that this paves the way to adjust the synthesis parameters in a way that the final morphology of the nano-LDH particles can be controlled to be either round or platelet-like.
CRIS-Team Scopus Importer:2020-04-02